(3GdJPcQI aj GdbQGAGJ Yf GdCFeI GdbQGAs - (3WGgQ Hf CMeO GdfMhj, CHh GdMSf,J (B380 (3g` s
(3ChdgG (B:s
(3CeG HYO MeOGddg HLejY eMGeOg aEfj PGcQ aj gPG GdcJGH Edi ef bQGAI GdCeUGQ GdeTghQjf HGdEjLGR s
(3BNQgG (B:s
(3aGdMed Ydi eGQSeJ dc ofUH GdUhGH hJQTO Ef TGA Gddg YR hLd s
(3GdfSNI HgG MhGTs
(3HChdgG bQGAI SfI (B602 (3g` hGdfSNI ebGHdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B392s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(282 (3b(B) s
Keywords: (3GdbQGAGJ hGdJLhjOs